Cerium oxide nanoparticles: green synthesis and biological applications - Charbgoo, Fahimeh (Int J Nanomedicine, 2017)
CeO(2) nanoparticles (NPs) have shown promising approaches as therapeutic agents in biology and medical sciences. The physicochemical properties of CeO(2)-NPs, such as size, agglomeration status in liquid, and surface charge, play important roles in the ultimate interactions of the NP with target cells. Recently, CeO(2)-NPs have been synthesized through several bio-directed methods applying natural and organic matrices as stabilizing agents in order to prepare biocompatible CeO(2)-NPs, thereby solving the challenges regarding safety, and providing the appropriate situation for their effective use in biomedicine. This review discusses the different green strategies for CeO(2)-NPs synthesis, their advantages and challenges that are to be overcome. In addition, this review focuses on recent progress in the potential application of CeO(2)-NPs in biological and medical fields. Exploiting biocompatible CeO(2)-NPs may improve outcomes profoundly with the promise of effective neurodegenerative therapy and multiple applications in nanobiotechnology.